Effect of the perception of electoral manipulation on voter participation - Deleña, Juan Antonio N.; Tablante, Heather Lian G.
Voting is an essential part of every election for democratic countries. However, an ever-pervasive issue concerning elections in the Philippines is electoral manipulation. In this study, we examine the Filipino’s perception on voter manipulation and likelihood to vote. By utilizing the May 2016 Official Pre-Election Survey of the Social Weather Station with a sample size of 4,500 Filipinos nationwide, we focus on the effect of demographic factors, socioeconomic factors, voting records, and perception of electoral manipulation on voter participation. This research is conducted by a probit model, bivariate probit model, and a recursive bi-probit model. With these models, we assess the effect of manipulation and education on the likelihood to vote. In addition to that, we will also assess the joint probability of voting and perception of manipulation and the likelihood of voting conditional to the presence of manipulation. The results of the study show that the perception of electoral manipulation does partially encourage an individual to vote. Moreover, education presents a notable positive effect on voting and perception of electoral manipulation. By conducting this study, the researchers show the importance of education to a present-day voter as it increases one’s likelihood to vote and strengthens one’s sense of citizenship.